Kajian Jumlah Kebutuhan Personil Air Traffic Controller (ATC) yang Ideal di LPPNPI Cabang Makassar - Nur, Muh. (Politeknik Penerbangan Makassar, 2018)
Air Traffic Controller (ATC) is a professional HR that provides services and controls air traffic to prevent planes from getting too close to one another, preventing collisions between aircraft and aircraft with obstacles in their surroundings during operation. The purpose of this study is to determine the ideal number of Air Traffic Controller (ATC) personnel in the Makassar Branch LPPNPI. The research method used is quantitative to assess the ideal number of Air Traffic Controller personnel to support the security, convenience and smoothness of air traffic services both to the ATC and air traffic service users based on KP 287 in 2015, and KP 218 in 2017. The results of this study by knowing the amount of ATC needs can improve work comfort and safety and smooth flight traffic in all units in the Makassar aviation traffic control center, in addition as a foundation for further research.